New Quick And Easy Publication - Will be edited by LibreCat team - Domenik Ackermann (Quick And Easy Journal Title)

New Quick And Easy Publication - Will be edited by LibreCat team - Domenik Ackermann (Quick And Easy Journal Title)

Mosaic Tiles: Comparative Theological Hermeneutics and Christian-Jewish Dialogue About the Land - Ackermann, Domenik (CrossCurrents)
Keywords: General Engineering

The Offering of Incense: Jewish Mystical Perspectives on Disease and Healing* - Ackermann, Domenik (Dialog)
Abstract An examination of a passage from the Zohar on Exodus (2:218b‐219b) provides Jewish mystical perspectives on disease, which may help inform a Christian response of solace and healing to illness and suffering in general, and to the COVID‐19 pandemic in particular. The aforementioned passage in the Zohar describes the preparation of incense. The primary purpose of the portion maintains that incense has special healing powers that even relieve people from severe diseases. The relating Midrash Ha‐Ne'lam explains the passage further by referring to the 4th century Palestinian Rabbi Aha arriving at a town that struggles with an epidemic. It describes how R. Aha initiates a ritual containing a study of the Talmud on incense, after which the village is healed from the epidemic. The Jewish theological background and reception of the passage may shed new light on how ritual and sensory experience can alleviate the experience of disease and suffering.
Keywords: Religious studies